Surface modification induced enhanced CO2sorption in cucurbit[6]uril, an organic porous material - Mohan, M.; Suzuki, T.; Nair, A.; Pillai, S.; Warrier, K.; Hareesh, U.; Nair, Balagopal; Gale, Julian (R S C Publications, 2017)
Â© 2017 the Owner Societies. The CO 2 adsorption properties of an organic macrocycle, cucurbit[6]uril (CB[6] ), have been evaluated through experimental and theoretical studies. Quantum mechanical calculations show that CB[6] is capable of adsorbing the CO 2 molecule selectively within its cavity relative to nitrogen. Adsorption experiments at 298 K and at 1 bar pressure gave a CO 2 adsorption value of 1.23 mmol g -1 for the unmodified material. Significant enhancements in the CO 2 adsorption capacity of the material were experimentally demonstrated through surface modification using physical and chemical methods. Ethanolamine (EA) modified CB[6] provided an excellent sorption selectivity value of 121.4 for CO 2 /N 2 at 323 K and is unique with respect to its discrimination potential between CO 2 and N 2 . The chemical nature of the interaction between CO 2 and amine is shown to be the primary mechanism for the enhanced CO 2 absorption performance.